Functional Specialization within the Supplementary Motor Area: A fNIRS Study of Bimanual Coordination - Wilson, Tony W. (2013)
Bimanual movements can be performed by flexing and extending the target effectors (e.g., hand muscles) in unison, or by flexing units on one side in unison with extension of the same units on the opposite side. The former movement patterns are generally referred to as in-phase or parallel, whereas the latter patterns are often termed anti-phase movements. It is well known that anti-phase patterns are unstable and tend to spontaneously transition to in-phase movements at higher repetition rates, but the mechanisms and brain regions involved are not fully understood. In the current study, we utilized functional near-infrared spectroscopy (fNIRS) to evaluate whether anterior/posterior subdivisions of the supplementary motor complex (SMA) have distinct functional roles in maintaining in-phase and anti-phase movement patterns. Twelve healthy adult participants completed a bimanual coordination task comprised of anti-phase and in-phase trials as 24-channel fNIRS data was recorded from dorsal-medial motor areas. We examined the relative concentrations of oxygenated and deoxygenated hemoglobin in the channels that were located over the anterior SMA (e.g., pre-SMA) and the SMA proper. Our most interesting results indicated that oxygenated hemoglobin responses were greater in the anterior SMA during performance of anti-phase compared to in-phase movements. In the SMA proper, oxygenated hemoglobin responses did not differ between the two movement patterns. These data suggest that the anterior SMA is critical to programming and maintaining the less stable anti-phase movement patterns, and supports the conceptual framework of an anterior-directed gradient of progressively more complex functionality in the SMA.